Sterilization and Traffic Management of The Ferry Port of Kalabahi - Alexander Hilmi Perdana; Surnata Surnata; Fathia Rahmania (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2019)
The Ferry Port of Kalabahi is a port managed by Service Unit of Transportation Center Business (BPTD) Region XIII Province of East Tenggara Timur . At this time in The Ferry Port Of Kalabahi there is no facility counters, counters available today still located outside the port area where it is out of the zoning system should be, the pickup can enter the dock area and wait on moveable bridges and catwalks, home moveable bridge that has not been sterile because there are still people who are not authorized to be in front of the moveable bridge. In addition, there is no orderly traffic in the Port of Kalabahi Ferries due to a meeting between the vehicle that will go to the dock with the introduction of two-wheelers / pickup that will come out of the harbor. To analyze this based orientation on Minister Of Transportation Regulation Number PM 29 of 2016 on Sterilization Port Of Ferries and Director-General Land Transportation Regulation Number: SK.242 / HK.104 / DRJD / 2010 on Technical Guidelines for Management of Traffic Ferries. The analysis used is the analysis of the zone system, traffic pattern analysis, and analysis equipment requirements and the number of support personnel sterilization and traffic management in the The Ferry Port of Kalabahi In order to ease the flow of traffic load both of which will enter the port area and the cargo to be out of the port area is to set back lanes of vehicles that will enter the dock area and vehicle introduction / pickup that will come out of the port area in addition to assign officers to manage traffic to run more orderly. Adding a user signs, weighbridge, Tollgate, road markings, safety officers in order to become a regular port.